Application of Modified Starch on Carrageenan-Based Bioplastic’s Cup From Eucheuma cottonii on Biodegradability and Water Resistance - Teprin Ani Triani; Mochammad Amin Alamsjah; Dwi Yuli Pujiastuti (Universitas Airlangga, 2022)
Polysaccharides from carrageenan have potential as bioplastics that is resistance to waters (hydrophobic), alsocan be improved by using modified starch. Modified starch is a material that can reduce the hydrophilic properties of bioplastics. The objectives of this study were to determine the effect of modified starch application on carrageenan-based bioplastic’s cup on biodegradability and water resistance and to determine the best bioplastic formulation for biodegradability and water resistance. This study was conducted using experimental methods in the biodegradation test and the resistance or swelling test. The experimental method in this study used a completely randomized design (CRD) at a significance level of 5% (α = 0.05). The results of this study indicate that the addition of high modified starch can increase the water resistance of bioplastics but the addition of high modified starch will result in slower biodegradability.